Correlation between structural, ion transport and ionic conductivity of plasticized 2-hydroxyethyl cellulose based solid biopolymer electrolyte - Hafiza M.N.; Isa M.I.N. (Elsevier B.V., 2024)
Indexed by WOS/Scopus/ERA